On the phylogeny of the late Albian genus Planomalina - Maria Rose Petrizzo; Brian T. Huber (2005)
The evolution of planktonic foraminifera in the late Albian is characterized by a high rate of turnover (extinction plus speciation) and by a high rate of diversification (speciation minus extinction) (see Leckie and others, 2002 and references herein). The accelerated speciation rate resulted in the appearance of new genera such as Biticinella, Rotalipora, Planomalina and Praeglobotruncana. Among these genera the planispiral and keeled genus Planomalina displays the shortest stratigraphic range, which is totally comprised within the uppermost Albian sediments. There has been a general consensus among most authors that the late Albian Planomalina lineage was derived from the genus Globigerinelloides (Moullade, 1966, Pessagno, 1967; Longoria, 1974; Wonders, 1975). However, opinions have varied regarding what was the ancestral species. Citing morphological similarities, such as the planispiral coiling mode and the acquisition of keel and raised sutures, Moullade (1966) and Wonders (1975) concluded that Globigerinelloides caseyi (=G. eaglefordensis in Moullade’s study) is the ancestral species of the Planomalina lineage through the evolutionary series from G. caseyi – P. praebuxtorfi - P. buxtorfi. Later Moullade and others (2002) inferred that Globigerinelloides bentonensis gave rise to the planomalinids by progressive development of a peripheral keel and raised sutures through coalescence of muricae. The conclusions of Moullade and others (2002) are based on their studies of topotypes of G. caseyi (the ‘boreal’ species) from the Gault of England and specimens of G. bentonensis (the ‘Tethyan’ species) from various upper Albian levels of ODP Site 1050. These authors believe that the two species are distinct, with the former characterized by a smooth, probably microperforate wall texture that is totally devoid of muricae, whereas G. bentonensis yields a macroperforate wall with moderately developed muricae that are mostly confined to the first chambers of the last whorl. Our re-examination of the primary type ...